1974
DOI: 10.1042/bj1380185
|View full text |Cite
|
Sign up to set email alerts
|

Fate of corticotrophins in an isolated adrenal-cell bioassay and decrease of peptide breakdown by cell purification

Abstract: 1. The fate of corticotrophins in a trypsin-dispersed rat adrenal-cell assay system was investigated with a view to establishing whether differences in the rate of inactivation might contribute to potency differences observed between analogues. 2. Corticotrophin-(1-24)-tetracosapeptide and to a lesser extent synthetic 1-39 corticotrophins were found to be inactivated during incubation with cell suspension. 3. Peptide fragments were isolated by using [[(3)H(2)]Tyr(23)]corticotrophin-(1-24)- tetracosapeptide as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

1974
1974
1988
1988

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(21 citation statements)
references
References 13 publications
1
20
0
Order By: Relevance
“…However, in an isolated adrenal cell system (Lowry, McMartin & Peters, 1973) the 1-24 peptide has been found to be several times more potent than the full sequence and it has been shown that the potency difference is not a result of different rates of inactiva¬ tion of the peptides in the assay system (Bennett, Bullock, Lowry, McMartin & Peters, 1974).…”
Section: Introductionmentioning
confidence: 99%
“…However, in an isolated adrenal cell system (Lowry, McMartin & Peters, 1973) the 1-24 peptide has been found to be several times more potent than the full sequence and it has been shown that the potency difference is not a result of different rates of inactiva¬ tion of the peptides in the assay system (Bennett, Bullock, Lowry, McMartin & Peters, 1974).…”
Section: Introductionmentioning
confidence: 99%
“…These acidic groups may interact with the basic core at residues 15-18 and impede the binding of ACTH to its receptor, thus providing a possible explanation for the observed differences in affinity between ACTH1-24 and ACTH1-39. Additional evidence for the interaction of these two domains is provided by the observation that ACTH1-39 is more resistant to proteolysis than is ACTH1-24; possibly, amino acids 25-39 protect the natural peptide against proteolytic degradation (30). These observations suggest that further investigations into the relative effects of ACTH 1-24 and ACTH are warranted.…”
Section: Discussionmentioning
confidence: 96%
“…ACTH has been shown to be rapidly degraded in vitro by both plasma (Purvis and Sirett, 1968) and adrenocortical cells (Voigt et al, 1974). Its degradation is enhanced by the presence of both (Voigt et al, 1974), is more rapid with denser cell populations, and may be due to proteases released into the medium from damaged (dying) cells (Bennett et al, 1974). Thus it is possible that even though we used maximal dosages of ACTH, significant degradation occurred in our cultures over 2 days, particularly at the high cell densities.…”
Section: General Morphology Of Isolated Cells Andmentioning
confidence: 92%